Elevation-dependent shift of landslide activity in mountain permafrost regions of the Qilian Mountains - Jie Chen; Jing Zhang; Tong-Hua Wu; Lin Liu; Fan-Yu Zhang; Jun-Ming Hao; Ling-Cao Huang; Xiao-Dong Wu; Peng-Ling Wang; Zhuo-Xuan Xia; Xiao-Fan Zhu; Pei-Qing Lou (Advances in Climate Change Research)
Increasing landslide activities in cold regions have been attributed to rising temperatures and consequent permafrost degradation. While previous studies have linked permafrost degradation to slope instability, the elevation-dependent effects of this degradation on landslide occurrences in the high-mountain regions of the Qinghai–Tibet Plateau (QTP) remain poorly understood, particularly concerning their spatial distribution and timing. This study addresses this gap by investigating the distribution and timing of landslides in the Babao River catchment, located in the southeastern Qilian Mountains of the northeastern QTP. Our results reveal a substantial increase in landslide events during the study period of 2009–2018: only 14 occurrences were recorded before and in 2009, 22 between 2010 and 2015, and 105 during 2016–2018. Notably, we observed an upward shift in the elevation of landslide occurrences, with an average increase of approximately 130 m over the ten-year period. Analysis of annual permafrost distribution maps indicates that this shift coincides with the rising lower altitudinal limit of mountain permafrost in the study area, likely driven by increased temperatures and precipitation. These findings highlight the critical role of elevation-dependent processes in influencing landslide dynamics under changing climatic conditions, particularly the transition from undisturbed permafrost to seasonally frozen ground at higher elevations. This study provides valuable insights for disaster prevention and mitigation in high-altitude regions, emphasizing the heightened risks posed by permafrost degradation under ongoing warmer and wetter climatic conditions.